The impact of using Bybee five stages Model on Morphological Concepts achievement for tenth grade students in Mafraq Governorate Derivatives as a Model: Experimental study - Jordan - Al-khawaldeh, Odeh Issa Khalf (Journal of Educational and Psychological Sciences, 2020)
The objective of the study is to reveal the effect of five stages model on achievement morphology concepts for the tenth-grade students in Mafraq, Sample of the study is formed from experimental group (27 Students) and the other group is controller group consist of (30 students). MDE. To achieve the goal of the study, the researcher prepared a list of morphology skill inspired by Bloom Cognitive form Also researcher built a morphology concepts achievement examination, according to these skills. and it was (20 questions) The researcher built a and guide for the teacher, and he explained the way to teach the morphological concepts according to Bybee five stages model After applying the study and performing statics The result of the study indicated a significant improvement in achieving the morphological concepts for the experimental group students results, with (32, 75) average, Comparing with the controller group students with (25, 16)average. the (t) value has calculated (3, 85) and statistical terms (0, 00) In the case of the study ends with several recommendations and practical implementations.
Keywords: Morphological Concepts; Bybee five stages model; Jordan; tenth grade